Social Forestry in Rajasthan - A Way of Life - Mathur, A. B.; Ghose, Abhijit (Indian Forester, 1991)
For food security through agricultural sustainabillty and drought proofing through ambitious greening programmes are twin needs before the state. Practically there is no scope for any forestry activities other than Social Forestry in Rajasthan. It is regarded more as a way of life. Not only it is challenging task for controlling desertification and preventing of further land degradation but call for an attitudinal change of people towards growing of tree with simultaneously achieveing self sufficiency in fuel, fodder and small timber requirements.